Pembrolizumab associated hypereosinophilia in locally advanced triple-negative breast cancer - Remo Poto; Antonio di Salvatore; Laura Stigliano; Elisabetta Simeone; Maria Teresa Narducci; Michela Williams; Alessandra Cuomo; Carlo Gabriele Tocchetti; Amato de Paulis; Gilda Varricchi (Exploration of Medicine)
The advent of immunotherapy has revolutionized the therapeutic landscape of breast cancer. The immune checkpoint inhibitor drug, pembrolizumab, a monoclonal antibody targeting programmed cell death protein 1 (PD-1), was recently approved by the Food and Drug Administration (FDA) as a neoadjuvant treatment in combination with traditional chemotherapy in locally advanced triple-negative breast cancer (LA-TNBC). This manuscript aims to highlight an uncommon adverse event of immune checkpoint inhibitors (ICIs): hypereosinophilia (HE). Herein, we report the case of AW, a 49-year-old female patient, who was treated for triple-negative breast cancer (TNBC) with pembrolizumab, achieving a complete response. After undergoing surgery, pembrolizumab was reintroduced as adjuvant therapy, at which point an abnormal increase in eosinophil count was observed. Hence, treatment was interrupted, and after glucocorticoid administration, the eosinophil count reverted to normality. Our findings underscore the necessity for vigilant monitoring of blood eosinophil levels during pembrolizumab therapy and provide insights into the management of such immunotherapy-related adverse events.